Collagen type IV alpha 6 promotes tumor progression and chemoresistance in ovarian cancer by activating the discoidin domain receptor 1 pathway - Yi-Hui Wu; Pei-Ying Wu; Yu-Fang Huang; Chien-Chin Chen; Soon-Cen Huang; Chou Cheng-Yang (Oncogenesis)
Abstract Biomarkers that predict disease progression may assist in the development of better therapeutic strategies for aggressive cancers, such as ovarian cancer. This study aimed to investigate the role of collagen type IV alpha 6 (COL4A6) in cell invasiveness, tumor formation, chemoresistance, and the prognostic impact of COL4A6 expression in ovarian cancer. COL4A6 regulated discoidin domain receptor 1 (DDR1)/p-DDR1 expression through the binding of E2F transcription factor 1 (E2F) to its putative DDR1 promoter binding site, suggesting that the E2F–DDR1 axis is upregulated by COL4A6. Pharmacological inhibition of DDR1 abrogated COL4A6-dependent cell invasiveness and chemoresistance. COL4A6 regulated cell invasion via the E2F1/DDR1/focal adhesion kinase axis; in contrast, COL4A6 regulated cell sensitivity to cisplatin via the DDR1/nuclear factor-kappa B axis. DDR1-IN-1 increased cell sensitivity to cisplatin, synergized with cisplatin to suppress the invasive ability and oncogenic potential of ovarian cancer cells, and decreased tumor formation in mouse xenografts. High COL4A6 mRNA levels were associated with advanced disease stages and poor chemotherapy response. The 5-year recurrence-free and overall survival rates were significantly lower in patients with high tissue COL4A6 mRNA expression levels than in those with low expression levels. COL4A6 may promote tumor aggressiveness and chemoresistance via the E2F/DDR1 axis, and COL4A6 expression can predict clinical outcomes in patients with ovarian cancer. DDR1 should be targeted in patients with COL4A6-positive tumors.